American Academy of Physicians' Associates: Minutes of Regular Academy Meeting - Stanhope, William D. (1973)
Minutes of the American Academy of Physicians' Associates Regular Meeting held at the Montefiore Medical Center, New York, NY on February 3, 1973. Three votes were taken: (1) to amend bylaws to make membership less restrictive, (2) to change name to American Academy of Physicians' Assistants, and (3) to merge with the American College of Physicians Assistants.